Mimicking the Organic and Inorganic Composition of Anabolic Bone Enhances Human Mesenchymal Stem Cell Osteoinduction and Scaffold Mechanical Properties - Mondragón, Eli; Cowdin, Mitzy; Taraballi, Francesca; Minardi, Silvia; Tasciotti, Ennio; Gregory, Carl A.; Kaunas, Roland (Frontiers in Bioengineering and Biotechnology, 2020)
Engineered bone graft designs have been largely inspired by adult bone despite functionally significant differences from the composition of anabolic bone in both the mineralized and non-mineralized fractions. Specifically, anabolic bone contains hydroxyapatite with ionic substitutions that facilitate bone turnover and relatively rare collagens type VI and XII that are important for normal bone development. In this work, human mesenchymal stem cells (hMSCs) were cultured in lyophilized collagen type I scaffolds mineralized with hydroxyapatite containing Mg2+ substitutions, then induced to deposit an extracellular matrix (ECM) containing collagens VI and XII by exposure to GW9662, a PPARγ inhibitor. Delivery of GW9662 was accomplished through either supplemented media or via composite microspheres embedded in the scaffolds for localized delivery. Furthermore, hMSCs and scaffolds were cultured in both static and perfuse conditions to investigate the interaction between GW9662 treatment and perfusion and their effects on ECM deposition trends. Perfusion culture enhanced cell infiltration into the scaffold, deposition of collagen VI and XII, as well as osteogenic differentiation, as determined by gene expression of osteopontin, BMP2, and ALP. Furthermore, scaffold mineral density and compressive modulus were increased in response to both GW9662 treatment and perfusion after 3 weeks of culture. Local delivery of GW9662 with drug-eluting microspheres had comparable effects to systemic delivery in the perfusate. Together, these results demonstrate a strategy to create a scaffold mimicking both organic and inorganic characteristics of anabolic bone and its potential as a bone graft.